Analisis Pemajanan Benzena terhadap Kadar Fenol dalam Urin dan Status Anemia pada Pekerja Sektor Industri Pengolahan Petroleum - Kusuma, Arnita Ayu; Setiani, Onny; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background : Benzene is known to cause blood disorders. The concentration of benzene in the workplace was above REL NIOSH, 0.1 ppm, so the workers of the  petroleum refining industry were the population at risk of acute myeloid leukemia (AML) when exposed to low level benzene (<1 ppm) in long duration. Anemia is one of the early detection of AML, and urinary phenol has done as one of  the biomarkers for benzene exposure in the end of the shifts. Method : Inhalation doses were assessed by organic vapour monitor (OVM), while urinary phenol level was measured by 4-aminoantipyrin method. Anemia status was categorized by haemoglobin level <13,5 gr/dL which was assessed by sianmethemoglobine method. Cross-sectional design and 42 samples were used in this study. Confounding factors, i.e: diet, alcohol consumption, lozenges using, personal protective equipment, recently infection, and duration of exposure were controlled in this study. Result : No significant associations between age,  body mass index, work duration, smoking habit, exposure to benzene and urinary phenol concentration. There were also no significant association between age, body mass index, smoking habit, exposure to benzene, urinary phenol level with anemia (all p-Kendall >0.05), but there was a significant correlation between smoking habit and urinary phenol level         (r-Kendall=-0.539 ; p=0.001). There was also a significant difference (p-Mann Whitney=0.001) for urinary phenol concentration between smokers and non-smokers. Analysis using multiple logistic regression showed smoking habit had potential effect to urinary phenol concentration ³ 10 mg/L (ATSDR 1998 normality standard), with OR=1.198 (95%CI:0.612-8.856). Conclusion : at low level exposure to benzene (<1 ppm), smoking may be regarded as the major source of benzene intake. Suppresion in hematological value (i.e. decreasing in amount of haemoglobin/anemia) had not seen yet in 3-16 years in jobs. Although no statistical significance results (except for smoking habit), annual medical surveillance is necessary to anticipate  adverse effect of exposure to low level benzene. Keywords : benzene, urinary phenol concentration, anemia, petroleum refinery industry.